Dual translational initiation sites control function of the lambda S gene. - Bläsi, U (1989)
Lysis gene S of phage lambda has a 107 codon reading frame beginning with the codons Met1-Lys2-Met3. Genetic data have suggested that translational initiation occurs at both Met1 and Met3, generating two polypeptides, S107 and S105 respectively. We have proposed a model in which the proper scheduling of lysis depends on the partition of translational initiations between the two start codons. Here, using in vitro methods, we show that two stem-loop structures, one immediately upstream of the reading frame and a second approximately 10 codons within the gene, control the partitioning event. Utilizing primer-extension inhibition or 'toeprinting', we show that the two S start codons are served by two adjacent Shine-Dalgarno sequences. Moreover, the timing of lysis supported by the wild-type and a number of mutant alleles in vivo can be correlated with the ratio of ternary complex formation over Met1 and Met3 in vitro. Thus the regulation of the S gene is unique in that the products of two adjacent in-frame initiation events have opposing function.